PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN STRESS KERJA TERHADAP KINERJA PEGAWAI PADA BADAN NARKOTIKA NASIONAL PROVINSI MALUKU UTARA - Risman S.A Rajak; Sri Ekanti Sabardini (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
The National Narcotics Agency of North Maluku Province is an Indonesian Non-Ministry Government Institution is one of representatives from 33 provinces throughout Indonesia which is located in Ternate City. This study aims to analyze the effect of motivation, work environment and work stress on employee performance at BNNP North Maluku. The sample in this study were 52 employees of the BNNP North Maluku. The sampling technique used was the Non-probability sampling model. The analytical method used is the method of multiple linear regression analysis, t test and coefficient of determination. The results of the data from this study are that motivation does not affect employee performance at BNNP North Maluku, work environment affects employee performance at BNNP North Maluku, and stress does not affect employee performance at BNNP North Maluku.